Peningkatan Efisiensi Waktu Kapal Sandar di Era New Normal Dipelabuhan Tanjung Emas Semarang - kumila Mila Hanik (Sekolah Tinggi Maritim Yogyakarta, 2021)
Currently the Marine Transportation Sector had quite hard challenge due to the existence of Covid - 19, so that services were hampered and not maximal, especially in the shipping industry sector which required the process of anchoring ships through several health protocol procedures. Therefore, the purpose of this study was to discuss and analyze the problems that arose in relation with the implementation of berthing by shipping agents in the New Normal period, and how the solutions were given. The method used in this research was to use the concept of information data; quality of information and value of information. The concept of information data was a processed data into a useful form to its user.From the results of the analysis, it was found that in order to make berthing time more efficient, shipping companies must implement a new policy issued by the Ministry of Transportation, Directorate General of Marine Transportation, Harbormaster’s Office and Port Authority Class 1 Tanjung Emas Port through Circular Number: UM. 001/09/19 / KSOP. Tg Emas - 2020 concerning the Establishment of a Quarantine Area at the quay, provided guidance and application of health protocols for ships that would be berthing in the aspects of health, social, economy and countermeasures for the corona virus spread in Tanjung Emas ​​Semarang area in the new normal era.